2020
DOI: 10.1186/s12885-020-6589-x
|View full text |Cite|
|
Sign up to set email alerts
|

Clinical and histopathological analyses of VEGF receptors peptide vaccine in patients with primary glioblastoma - a case series

Abstract: Background: The expression of vascular endothelial growth factor (VEGF)-A/ VAGF receptors (VEGFRs) signaling plays a pivotal role in the tumor angiogenesis and the development of the immunosuppressive tumor microenvironment in glioblastomas. We have previously conducted exploratory clinical studies investigating VEGFRs peptide vaccination with and without multiple glioma oncoantigens in patients with recurrent high-grade gliomas. Recently, an exploratory clinical investigation of VEGFRs peptide vaccination was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 48 publications
0
14
0
Order By: Relevance
“…We have previously conducted exploratory clinical trials investigating VEGFRs peptide vaccination with and without multiple glioma oncoantigens (LY6K, DEPDC1, KIF20A, and FOXM1) in patients with primary and recurrent malignant gliomas (UMIN000013381 (jRCTs031180170), UMIN000012774 (jRCTs031180148), and UMIN000005545) [14,22,23]. The inclusion and exclusion criteria were shown in our previous studies [14,22,23]. The Keio University School of Medicine Ethics Committee approved the trials, which were conducted in accordance with the Helsinki declaration on experimentation on human subjects.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We have previously conducted exploratory clinical trials investigating VEGFRs peptide vaccination with and without multiple glioma oncoantigens (LY6K, DEPDC1, KIF20A, and FOXM1) in patients with primary and recurrent malignant gliomas (UMIN000013381 (jRCTs031180170), UMIN000012774 (jRCTs031180148), and UMIN000005545) [14,22,23]. The inclusion and exclusion criteria were shown in our previous studies [14,22,23]. The Keio University School of Medicine Ethics Committee approved the trials, which were conducted in accordance with the Helsinki declaration on experimentation on human subjects.…”
Section: Methodsmentioning
confidence: 99%
“…They were associated with favorable event-free survival and improvement of peritumoral edema, leading to a better patient performance status [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 ]. Bev is currently used most frequently in the management of glioblastomas [ 14 , 15 ]. However, clinical trials using these anti-angiogenic agents have suggested that the favorable clinical effects on patients’ performance status do not translate into an overall survival benefit.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of MAGE-A3 peptide vaccine as cancer therapeutic agent has resulted in a big disappointment as no significant clinical benefit was observed in two Phase III clinical trials (MAGRIT and DERMA) for patients with non-small cell lung cancer and melanoma ( Vansteenkiste et al, 2016 ; Dreno et al, 2018 ). To circumvent the lack of response to peptide vaccine, new studies are designed to target more than one antigen to avoid the risk for tumor escape due to antigen loss and to combine these vaccines with other approved therapies, for example, chemotherapy and checkpoint blockade inhibitors ( Kanekiyo et al, 2018 ; Kawamura et al, 2018 ; Noguchi et al, 2020 ; Tamura et al, 2020 ). The use of RNF43/TOMM3 peptide vaccine in combination with chemotherapy in metastatic colorectal cancer has demonstrated significantly better 3-year relapse-free survival in patients who have higher T cell responses compared to the negative response subgroup ( Kawamura et al, 2018 ).…”
Section: The Landscape Of Cancer Vaccinesmentioning
confidence: 99%
“…When the tumor grows to a thickness of more than 2 mm, the cells in the nucleus are farther away from the blood supply, and the exposure of cancer cells to certain hypoxic stimuli [ 9 , 11 ] is the main trigger for initiating a series of reactions involving diverse molecular processes; for example, expression of hypoxia-inducible factors (HIF) that stimulate the expression of vascular endothelial growth factors (VEGFs) by tumor cells [ 8 , 9 , 12 ], in addition to communication with its auxiliary cells that stimulate the formation of other growth factors, such as platelet-derived growth factors (PDGFs) [ 12 , 13 , 14 , 15 ] and epidermal growth factors (EGFs) [ 10 , 16 , 17 ]. In chemotactic communication, inflammatory cells are recruited, such as tumor-associated macrophages (TAMs), which, in turn, stimulate a chain reaction of continuous tumor growth, intensifying the signaling of hypoxia to tumor cells, which further stimulates the expression of HIF and, mainly, VEGF [ 18 , 19 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%